2012
DOI: 10.5539/jsd.v5n12p40
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Physical Transportation Infrastructure Vulnerable to Sea Level Rise

Abstract: The objective of this research was developing a methodology for assessing the potential impacts of sea level rise (SLR) on Florida's state transportation infrastructure to assist the state with transportation planning. The proposed approach integrates the Florida Department of Transportation (FDOT) information system, satellite imagery, local roadway and hydrologic data with existing topographical and geographical data to generate SLR projections to facilitate i) the evaluation of current and projected SLR imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…zone 145 to reduce negative SLR-related hazards that drive migration. Accommodation strategies include elevating homes and structures 55,155,156 , flood proofing 157 , managing land use, deploying flood warnings and pumps 158 , changing groundwater-extraction techniques 145 or elevating roads. Many port cities' coastal management plans already contain provisions to accommodate higher water levels 155 , such as coastal buffer zones in Ghana 159 or multi-tiered terraces in Mokpo, Korea 160 .…”
Section: Institutional Influencesmentioning
confidence: 99%
“…zone 145 to reduce negative SLR-related hazards that drive migration. Accommodation strategies include elevating homes and structures 55,155,156 , flood proofing 157 , managing land use, deploying flood warnings and pumps 158 , changing groundwater-extraction techniques 145 or elevating roads. Many port cities' coastal management plans already contain provisions to accommodate higher water levels 155 , such as coastal buffer zones in Ghana 159 or multi-tiered terraces in Mokpo, Korea 160 .…”
Section: Institutional Influencesmentioning
confidence: 99%
“…In reality, lack of hydrologic connectivity inland may mean that those roads further inland may be protected against the coastal flooding scenarios examined in this paper. That said, the inland roads not hydrologically connected to the sea through surface water, may still be impacted by rising sea levels due to the associated rise in groundwater tables (Bloetscher 2012). The incorporation of rising groundwater levels in the surficial aquifer into the modeling of roadway flooding would be an important enhancement to the analysis as a more comprehensive picture of sea level rise effects.…”
Section: Assumptions and Limitationsmentioning
confidence: 99%
“…LiDAR data, to identify vulnerable transportation infrastructure. Bloetscher et al (2012) studied the effect of a rising groundwater table in their flooding model. Instead of focusing on the physical infrastructure itself, Suarez et al (2005) modeled flood impacts on a transportation system's performance using lost trips and delay times as measures of disruption.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work by the authors in Broward and Miami-Dade Counties indicated significant risk to existing and future populations due to the low lying land (50% of the urban area is under 5 ft. NAVD88-see [19] [30] [33]- [35]). Palm Beach County is located just north of Broward and Miami-Dade Counties.…”
Section: Introductionmentioning
confidence: 99%